2020
DOI: 10.1002/adbi.202000129
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Click Hydrogels for Xeno‐Free Culture of Induced Pluripotent Stem Cells

Abstract: 3D cell-laden hydrogels are increasingly used for in vitro and ex vivo cell expansion, controlled stem cell differentiation, and regenerative medicine. [1] Hydrogels can be fabricated by derivatives of purely synthetic polymers (e.g., poly(ethylene glycol) or PEG) and/or naturally derived biomacromolecules (e.g., gelatin, hyaluronic acid, or heparin). [2] Tumor basement membrane derived Matrigel is routinely used as a convenient matrix for 3D cell culture owing to its inherent cell affinity provided by laminin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 63 publications
2
40
0
Order By: Relevance
“…By encapsulating iPSCs in thiol-norbornene cross-linked PEG hydrogels, the authors demonstrated that dynamic hydrogels resulted in remarkably higher cell survival than static hydrogels did. 367 You et al developed a photodegradable "heparin photogel" to differentiate mouse ESCs into definitive endoderm. To fabricate such hydrogels, thiolated heparin molecules were cross-linked by PEGs with bifunctional acryl-terminated photolabile o-nitrobenzyl moieties.…”
Section: Stem Cells and Regenerative Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…By encapsulating iPSCs in thiol-norbornene cross-linked PEG hydrogels, the authors demonstrated that dynamic hydrogels resulted in remarkably higher cell survival than static hydrogels did. 367 You et al developed a photodegradable "heparin photogel" to differentiate mouse ESCs into definitive endoderm. To fabricate such hydrogels, thiolated heparin molecules were cross-linked by PEGs with bifunctional acryl-terminated photolabile o-nitrobenzyl moieties.…”
Section: Stem Cells and Regenerative Medicinementioning
confidence: 99%
“…Pluripotent stem cells include both embryonic stem cells (ESCs) derived from the inner cell mass of blastocyst-stage embryos and induced pluripotent stem cells (iPSCs) reprogrammed from mature, terminally differentiated cells. , These cells are traditionally cultured on feeder layers of mouse embryonic fibroblasts or reconstituted basement membrane derived from mouse sarcoma (e.g., Matrigel), although a growing number of xeno-free, chemically defined dynamic hydrogels have been developed for the in vitro culture of these cells in recent years. …”
Section: Biomedical Applications Of Dynamic Hydrogelsmentioning
confidence: 99%
“…Taking advantage of the dual reactivity of the norbornene group towards thiol and tetrazine moieties, our group has recently reported orthogonal PEG-peptide thiol-norbornene hydrogels for culture and differentiation of human-induced pluripotent stem cells (hiPSCs). In particular, hiPSC-laden hydrogels were dynamically stiffened using tetrazine-modified macromers [ 81 ].…”
Section: Mimicking a Stiffening Matrix Using Dynamic Hydrogelsmentioning
confidence: 99%
“…PEG-based thiol-norbornene hydrogels are known for their high cytocompatibility for in situ cell encapsulation. ,,, The PEGNB CA hydrogels also showed excellent cytocompatibility, as exemplified by the encapsulation of human induced pluripotent stem cells (hiPSC), dental pulp stem cells (DPSC), and PANC-1 human pancreatic cancer cells (Figure ). All hydrogels were cross-linked by matrix metalloproteinase (MMP)-sensitive peptide linker (i.e., KCGPQG*IWGQCK, *cleavage site) to permit cell-mediated matrix remodeling and immobilized with 1 mM RGDS peptide to support cell survival.…”
mentioning
confidence: 99%